PENINGKATAN KOMPETENSI PEDAGOGIK GURU MELALUI KEGIATAN SUPERVISI AKADEMIK DI SMK NEGERI 1 BANYUPUTIH SITUBONDO: SMK NEGERI 1 BANYUPUTIH SITUBONDO - SIGIT HINDARUM (Dewan Pendidikan Bondowoso, 2021)
The purpose of this action research is to 1). Improving the pedagogic competence of teachers, especially in the learning process through academic supervision. 2). Knowing the right steps in carrying out academic supervision in order to improve the pedagogic competence of teachers. This type of research is school action research because this research is carried out to solve problems in the classroom and is carried out in accordance with the steps in school action research. Classroom action research is carried out by starting with a systematic study of a problem. The results of the study are used as the basis for solving problems. This research was conducted at SMK Negeri 1 Banyuputih Situbondo which is located at Jalan KH A Zaini Dahlah Binding Sumber Banyuputih Situbondo for 3 months, from September to November 2018. The research subjects were teachers who taught class X SMK Negeri 1 Banyuputih Situbondo with a total of 14 teachers consisting of 9 PNS teachers and 5 non-permanent teachers (GTT). SMK Negeri 1 Banyuputih as an object as well as a subject in providing academic supervision treatment. The data collection technique in this research is through academic supervision which includes . 1). Supervise learning administration. 2). Supervise the implementation of learning in class Looking at the data from the Action research, the pedagogic competence of teachers in the implementation of the learning process has increased through academic supervision. Cycle I achieved an average pedagogical competence of 66% (enough) and in cycle II there was an increase in the average pedagogical ability of teachers to 76% (good). With the academic supervision activities there was a significant increase in the initial conditions of the school when compared to the final state in cycle II. The accuracy of teachers entering the classroom increased to 78%, the use of learning media increased to 72%, varied methods increased to 76%, and learning strategies also increased to 76%